Enhancing human strength via neural modulation: mechanisms of maximal voluntary contraction and translational interventions - Takarada, Yudai (Frontiers in Physiology, 2025)
Maximal voluntary contraction (MVC) is a key determinant of human strength, mobility and functional performance. While muscle morphology contributes to MVC force, neural factors—particularly cortical and spinal excitability and inhibition—play a central role in motor unit recruitment. Despite its importance, the neurophysiological mechanisms regulating MVC remain underrepresented in literature. This narrative review synthesizes current evidence on the neural substrates of MVC, including intracortical inhibition, descending drive, afferent feedback, and neuroplasticity within the primary motor cortex (M1) and the corticospinal tract. A structured search of PubMed and Google Scholar identified studies examining both mechanisms and interventions. Intervention strategies were categorized into four domains: cognitive-behavioral techniques (e.g., verbal encouragement, unconscious goal priming), afferent-driven approaches, pharmacological modulation, and neuromodulatory stimulation. Studies were appraised for methodological rigor and translational relevance, highlighting the latent capacity of the motor system to exceed conventional MVC thresholds through targeted modulation of excitatory and inhibitory circuits. Evidence supports the efficacy of neuromodulatory and cognitive interventions in enhancing MVC force, particularly in older adults, athletes, and clinical populations. However, variability in protocols and outcome measures limits the comparability across studies. Further research is warranted to clarify the neurophysiological basis of MVC enhancement and to develop optimized, context-specific strategies for rehabilitation and performance.